Conductive lithium-supplementing composite slurry, preparation method and application thereof, positive pole piece and battery
By using conductive lithium-supplement composite slurry, the problems of low pulping efficiency of lithium-ion batteries and prone to failure of lithium-supplement agents are solved, achieving high-efficiency pulping, stable performance and low-cost production.
Patent Information
- Application Number
- CN202411881110.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
The positive electrode pulping efficiency of existing lithium-ion batteries is low, and the lithium supplement agent is prone to failure, and reacting with the binder leads to gel problems, affecting battery performance.
The conductive lithium supplement composite slurry is used to make a stable slurry by using conductive agent, lithium supplement agent, solvent NMP, and thickener to make the conductive agent and lithium supplement agent evenly disperse it by ultrasonic dispersion and mechanical stirring to form a stable conductive lithium supplement composite functional slurry, which is used for the preparation of the positive electrode slurry.
It improves pulping efficiency, reduces the failure risk of lithium supplements, avoids gel problems, enhances the performance of the battery and the convenience of storage and transportation, and simplifies the process and reduces costs.
Smart Images

Figure CN119627112A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery materials, and in particular relates to a conductive lithium-supplementing composite slurry, a preparation method thereof, an application thereof, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries are widely used in various portable electronic devices, electric vehicles and other fields due to their high energy density, long cycle life and environmental protection. Lithium supplements can supplement lithium ions to offset irreversible lithium loss during the use of lithium-ion batteries, which can significantly improve the capacity and cycle performance of lithium-ion batteries. More and more lithium-ion battery manufacturers have begun to add lithium supplements to lithium-ion batteries, among which lithium supplements such as lithium-rich ferrite (Li5FeO4, abbreviated as LFO) and lithium-rich nickel oxide (Li2NiO2, abbreviated as LNO) are the most widely used. In the process of lithium-ion battery positive electrode slurry, conductive agent slurry and lithium supplements are two commonly added auxiliary materials. However, the more types of auxiliary materials are added, the more stirring steps there are, and the longer the positive electrode slurry takes, which is not conducive to improving production efficiency. In addition, commonly used lithium supplements such as lithium-rich ferrite and lithium-rich nickel oxide have poor air stability. When exposed to air, they are easy to react with moisture and carbon dioxide, resulting in performance deterioration. Direct use in the form of powder is not conducive to the preservation and use of such lithium supplements. Finally, the lithium-rich lithium iron oxide and lithium-rich lithium nickel oxide that have failed after reacting with air show strong alkalinity, and can easily react with the binder PVDF during positive electrode slurrying to form positive electrode slurry gel.
[0003] In the prior art, lithium supplement agents are usually added directly to the positive electrode slurry in the form of powder during slurry preparation. In order to improve the problem of lithium supplement agents being sensitive to air, existing patents generally use carbon coating methods, such as CN115642232A and CN117199276A. Nano-scale conductive agents such as carbon tubes and graphene are generally used in the form of conductive slurries, and there are no published patents for composite functional slurries of conductive agents and lithium supplement agents. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a conductive lithium-supplementing composite slurry and its preparation method, application, positive electrode plate and battery, which solves the problem of low slurrying efficiency and the problem of easy failure of the lithium-supplementing agent. Gel is not easy to appear in the positive electrode slurrying process. At the same time, the preparation process is simple and the cost is low, which not only saves energy and time in the preparation process, but also reduces production costs.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A conductive lithium-supplementing composite slurry comprises a conductive agent, a lithium-supplementing agent and a solvent, and does not contain a binder PVDF.
[0006] The conductive lithium-supplementing composite slurry mentioned above preferably further includes a thickener, and the thickener includes one or more of polyvidone (PVP), methyl cellulose (MC), ethyl cellulose (EC), hydroxypropyl methyl cellulose (HPMC) and hydroxyethyl cellulose (HEC).
[0007] The conductive lithium-supplementing composite slurry of the present invention has two functions: conduction and lithium replenishment. The solvent used is N-methylpyrrolidone (NMP), which is the solvent used in preparing the positive electrode slurry. In the present invention, the conductive agent, the lithium replenisher, NMP, and the thickener are made into a stable slurry, and the conductive agent and the lithium replenisher are uniformly dispersed in the mixed solution of NMP and the thickener by ultrasonic dispersion and mechanical stirring. The thickener acts as a stabilizer to form a stable conductive lithium-supplementing composite functional slurry. The slurry not only dilutes the concentration of the lithium replenisher but also isolates air and moisture, greatly reducing the sensitivity of the lithium replenisher to air and moisture. At the same time, the composite slurry has the dual functions of increasing the conductivity of the positive electrode and replenishing lithium. No additional conductive agent is required when making the positive electrode slurry.
[0008] In the above conductive lithium-supplementing composite slurry, preferably, the mass ratio of the conductive agent, lithium-supplementing agent, thickener and solvent is 0.1-10: 1-20: 0.3-5: 100. Controlling the mass ratio of the conductive agent, lithium-supplementing agent, thickener and NMP within the above range is conducive to ensuring that the slurry is within the optimal viscosity range, otherwise the slurry is unstable and easy to stratify if the viscosity is too low, and it is not easy to mix evenly if the viscosity is too high.
[0009] In the above-mentioned conductive lithium-supplementing composite slurry, preferably, the conductive agent comprises a nanoscale conductive agent and a carbon black conductive agent, the nanoscale conductive agent comprises one or more of single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (CNT), graphene (G) and vapor grown carbon fiber (VGCF), and the carbon black conductive agent comprises one or more of Super P Li (SP), Ketjen black (KB), acetylene black (ACET) and 350G; the mass ratio of the nanoscale conductive agent to the solvent is (0.1-5):100, and the mass ratio of the carbon black conductive agent to the solvent is (1-10):100.
[0010] In the above-mentioned conductive lithium-supplementing composite slurry, preferably, the lithium-supplementing agent includes one or two of lithium-rich lithium iron oxide (Li5FeO4) and lithium-rich lithium nickel oxide (Li2NiO2), and the solvent is N-methylpyrrolidone.
[0011] As a general technical concept, the present invention also provides a method for preparing a conductive lithium-supplementing composite slurry, comprising the following steps: Under a dry environment, conductive agent powder, lithium supplement agent powder, thickener and solvent N-methylpyrrolidone are weighed, the thickener is mechanically stirred and dissolved in the solvent, and then the nano-scale conductive agent is added for ultrasonic dispersion, and then the carbon black conductive agent is added for mechanical stirring and dispersion, and finally the lithium supplement agent is added and stirred under vacuum conditions to obtain a uniform suspension, and the conductive lithium supplement composite slurry is obtained after adjusting the viscosity and removing bubbles.
[0012] In the above preparation method, preferably, the viscosity of the conductive lithium-supplementing composite slurry is 3000-20000 mPa.s, and the slurry fineness is ≤30 μm; the environmental conditions are dew point ≤-40°C, and the vacuum degree during vacuum stirring is ≤-90 kPa.
[0013] As a general technical concept, the present invention also provides an application of the above-mentioned conductive lithium-replenishing composite slurry, wherein the conductive lithium-replenishing composite slurry is used for the preparation of positive electrode slurry, the positive electrode slurry contains a binder PVDF, and no other conductive agent and lithium-replenishing agent need to be added during the preparation, and the conductive lithium-replenishing composite slurry is added after the raw materials of the positive electrode material are dispersed and before the viscosity adjustment step (that is, the binder PVDF is first dispersed using the solvent NMP, and then the positive electrode active material is added for dispersion, and then the above-mentioned conductive lithium-replenishing composite slurry is added for dispersion); the amount of the conductive lithium-replenishing composite functional slurry is calculated according to the mass ratio of the sum of the mass of the conductive agent and the lithium-replenishing agent to the mass of the positive electrode active material of 0.5-10:100 (more preferably 0.5-2:100).
[0014] When exposed to air, the lithium supplement agent easily reacts with moisture and carbon dioxide, resulting in performance deterioration. This deterioration process is very easy to occur, whether it is during the production, packaging or use of the lithium supplement agent. It is difficult to avoid even if the slurry preparation process is in a vacuum environment. The present invention adopts multiple measures to solve this problem. The first measure is to make a slurry to protect the lithium supplement agent. The second is to make a slurry and add it to the positive electrode slurry when using it. The mixing speed of liquid and liquid is faster than that of solid powder. The subsequent process can be carried out after mixing for a short time, which reduces the reaction time and avoids long-term contact with the binder.
[0015] In the process of positive electrode slurrying, after the other raw materials (binder and positive electrode active material) are dispersed, the prepared conductive lithium-replenishing composite slurry is finally added, and the conductive lithium-replenishing composite slurry and the positive electrode are evenly mixed by mechanical stirring. The conductive lithium-replenishing composite slurry is used in the form of a suspension slurry, which not only simplifies the positive electrode slurrying process, but also has a better mixing effect and a shorter mixing time.
[0016] As a general technical concept, the present invention also provides a positive electrode plate, which includes a positive electrode collector and a positive electrode membrane disposed on the positive electrode collector, wherein the positive electrode membrane contains the above-mentioned conductive lithium-supplementing composite slurry.
[0017] As a general technical concept, the present invention also provides a lithium-ion battery, including the above-mentioned positive electrode plate.
[0018] Compared with the prior art, the advantages of the present invention are: (1) By making the conductive agent, lithium supplement agent, NMP and thickener into a stable slurry, the sensitivity of the lithium supplement agent to air and moisture is effectively reduced, the problem of the lithium supplement agent's easy failure is solved, and its use effect and convenience of storage and transportation are improved.
[0019] (2) The conductive lithium-supplementing composite slurry of the present invention replaces the traditional method of adding and stirring the conductive agent and the lithium-supplementing agent separately, and the process flow is shorter. In addition, the conductive agent and the lithium-supplementing agent are added to the positive electrode slurry in the form of a suspension, and the liquid-liquid mixing makes liquid mixing easier, which reduces the mixing time and improves the work efficiency.
[0020] (3) The present invention adds the conductive lithium supplement composite slurry in the last step of positive electrode slurry preparation, mixes evenly and then applies it, thereby avoiding the slurry gel problem during positive electrode slurry preparation caused by premature reaction of the lithium supplement agent with the binder PVDF in the positive electrode slurry, improving the stability of the positive electrode slurry, and thus improving the performance of the battery.
[0021] (4) The technical solution of the present invention has a simple process and low cost. Compared with the prior art, it not only saves energy and time in the preparation process, but also reduces production costs, and has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The invention discloses a preparation and application process of the conductive lithium-supplementing composite slurry.
[0024] Figure 2 It is the charging curve diagram of Example 1 and Comparative Examples 1 and 2.
[0025] Figure 3 It is the charging curve diagram of Example 5 and Comparative Examples 3 and 4. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0027] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0029] The conductive lithium-supplementing composite slurry proposed by the present invention is prepared as shown in the attached Figure 1 As shown, first, under dry conditions, weigh the conductive agent powder, lithium supplement agent powder, thickener and solvent NMP according to a certain ratio, dissolve the thickener in the solvent by mechanical stirring, then add the nano-scale conductive agent for ultrasonic dispersion, add the carbon black conductive agent and perform mechanical stirring, and finally add the lithium supplement agent and stir under vacuum to obtain a uniform suspension, add an appropriate amount of solvent NMP to make the slurry reach a suitable viscosity, and remove the bubbles generated by stirring to obtain a conductive lithium supplement composite functional slurry. The application method of the conductive lithium supplement composite functional slurry is as follows Figure 1 As shown, the conductive lithium supplement composite functional slurry is added before the viscosity adjustment step of the positive electrode stirring, and after being evenly mixed, the viscosity is adjusted and bubbles are removed to obtain the positive electrode slurry with the lithium supplement added.
[0030] Embodiment 1: (1) When the ambient dew point is ≤ -40°C, according to the formula in Example 1 (Table 1) (SWCNT:SP:LFO:PVP:NMP=0.1:4:4:1:100), weighed NMP and PVP are added into a stirring kettle and stirred until PVP is completely dissolved.
[0031] (2) Add nano-scale conductive agent SWCNT and perform ultrasonic dispersion until the mixture is uniformly mixed.
[0032] (3) Add carbon black conductive agent SP and perform mechanical stirring.
[0033] (4) Add the weighed lithium supplement LFO into the stirring kettle, stir under -90 kPa vacuum condition until the lithium supplement is evenly dispersed, add an appropriate amount of NMP to make the slurry viscosity in the range of 5000-15000 mPa.s, and obtain a conductive lithium supplement composite functional slurry after removing bubbles.
[0034] (5) According to the concentration of the prepared conductive lithium-supplementing composite functional slurry, weigh the materials according to the sum of the mass of the conductive lithium-supplementing agent it contains: lithium cobalt oxide (4.5V high voltage type): binder in a ratio of 4.05:100:2. In the process of positive electrode slurry preparation, when the other raw materials are mixed evenly, the conductive lithium-supplementing composite functional slurry is finally added, and the mixture is mechanically stirred in a double planetary stirring kettle to obtain a positive electrode slurry. After degassing and filtering, it is coated on the positive electrode current collector with a coater. Then, after drying, rolling and other processes, the positive electrode sheet is obtained. Keep a part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are carried out. The results are shown in Table 1 and Figure 2 As shown, the slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium cobalt oxide in comparative example 1, the charge capacity of lithium supplement LFO was calculated to be 785.1 mAh / g. The positive electrode slurry preparation took 8 hours.
[0035] Embodiment 2: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 2 in Table 1.
[0036] (2) The positive electrode slurry preparation steps and other material amounts are the same as in Example 1, and the amount of conductive lithium-supplementing composite functional slurry is shown in Example 2 in Table 1.
[0037] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium cobalt oxide in Comparative Example 1, the charge capacity of lithium supplement LFO was calculated to be 780.5 mAh / g. The positive electrode slurry preparation took 8 hours.
[0038] Embodiment 3: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 3 in Table 1.
[0039] (2) The positive electrode slurry preparation steps and other material amounts are the same as in Example 1, and the amount of conductive lithium-supplementing composite functional slurry is shown in Example 3 in Table 1.
[0040] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium cobalt oxide in Comparative Example 1, the charge capacity of lithium supplement LFO was calculated to be 784.1 mAh / g. The positive electrode slurry preparation took 8 hours.
[0041] Embodiment 4: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 4 in Table 1.
[0042] (2) The positive electrode slurry preparation steps and other material amounts are the same as in Example 1, and the amount of conductive lithium-supplementing composite functional slurry is shown in Example 4 in Table 1.
[0043] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium cobalt oxide in Comparative Example 1, the charge capacity of lithium supplement LFO was calculated to be 792.6 mAh / g. The positive electrode slurry preparation took 8 hours.
[0044] Embodiment 5: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 5 in Table 1.
[0045] (2) The positive electrode slurry preparation steps and other material amounts are the same as in Example 1. The amount of conductive lithium-supplementing composite functional slurry is shown in Example 5 in Table 1.
[0046] (3) The test results are shown in Table 1 and Figure 3 As shown, the slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium nickel cobalt manganese oxide in comparative example 3, the charge capacity of lithium supplement LNO was calculated to be 457.5 mAh / g. The positive electrode slurry preparation took 8 hours.
[0047] Embodiment 6: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 6 in Table 1.
[0048] (2) The positive electrode slurry preparation steps and other material dosages are the same as in Example 1. The dosage of the conductive lithium-supplementing composite functional slurry is shown in Example 6 in Table 1.
[0049] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium nickel cobalt manganese oxide in Comparative Example 3, the charge capacity of the lithium supplement LNO was calculated to be 445.5 mAh / g. The positive electrode slurry preparation took 8 hours.
[0050] Embodiment 7: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 7 in Table 1.
[0051] (2) The positive electrode slurry preparation steps and other material amounts are the same as in Example 1. The amount of conductive lithium-supplementing composite functional slurry is shown in Example 7 in Table 1.
[0052] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of lithium nickel cobalt manganese oxide in Comparative Example 3, the charge capacity of the lithium supplement LNO was calculated to be 454.8 mAh / g. The positive electrode slurry preparation took 8 hours.
[0053] Embodiment 8: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 8 in Table 1.
[0054] (2) The positive electrode slurry preparation steps and other material dosages are the same as in Example 1. The dosage of the conductive lithium-supplementing composite functional slurry is shown in Example 8 in Table 1.
[0055] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of the lithium-rich manganese-based in Comparative Example 5, the charge capacity of the lithium supplement LFO was calculated to be 780.8 mAh / g. The positive electrode slurry preparation took 8 hours.
[0056] Embodiment 9: (1) The environmental requirements and preparation steps for the conductive lithium-replenishing composite functional slurry are the same as those in Example 1. The formula of the conductive lithium-replenishing composite functional slurry is shown in Example 9 in Table 1.
[0057] (2) The positive electrode slurry preparation steps and other material dosages are the same as in Example 1. The dosage of the conductive lithium-supplementing composite functional slurry is shown in Example 9 in Table 1.
[0058] (3) The test results are shown in Table 1. The slurry preparation process and the slurry standing for 8 hours did not gel. After deducting the charge capacity of the lithium-rich manganese-based in Comparative Example 5, the charge capacity of the lithium supplement LFO was calculated to be 787.8 mAh / g. The positive electrode slurry preparation took 8 hours.
[0059] Table 1: Experimental conditions and test results of embodiments and comparative examples
[0060] Comparative Example 1: (1) Environmental requirements are the same as those in Example 1. Materials are weighed according to the formula SWCNT: SP: lithium cobalt oxide (4.5V high voltage type): binder in a ratio of 0.05:2:100:2. Among them, SWCNT is a conductive agent slurry with a content of 0.4%. A double planetary stirring kettle is used for mechanical stirring. First, an appropriate amount of NMP is added, and the binder is dispersed, the conductive agent SP is dispersed (taking 2 hours), and the lithium cobalt oxide is dispersed in turn. Finally, SWCNT is added for dispersion. Continue to add an appropriate amount of NMP to adjust the slurry to a suitable viscosity, and remove bubbles to obtain a positive electrode slurry. Use a coater to apply the slurry to the positive electrode collector. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. Retain part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are carried out. The results are shown in Tables 1 and Figure 2 As shown, the slurry preparation process and the slurry standing for 8 hours did not gel. The charge capacity of lithium cobalt oxide in Comparative Example 1 was 195.12 mAh / g. The positive electrode slurry preparation took 10 hours.
[0061] Comparative Example 2: The environmental requirements are the same as those in Example 1. Except for the slurry with a SWCNT content of 0.4%, the remaining materials are solid powders. Weigh the materials according to the formula SWCNT: SP: LFO: lithium cobalt oxide (4.5V high voltage type): binder in a ratio of 0.05:2:2:100:2. Using a double planetary stirring kettle for mechanical stirring, first add an appropriate amount of NMP, and then disperse the binder, the conductive agent SP (taking 2 hours), the LFO (taking 2 hours), the lithium cobalt oxide, and finally add SWCNT to disperse. Continue to add an appropriate amount of NMP to adjust the slurry to a suitable viscosity, remove bubbles to obtain the positive electrode slurry. Use a coater to apply the slurry to the positive electrode collector. Then, after drying, rolling and other processes, the positive electrode sheet is obtained. Retain part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and first effect tests are carried out. The results are shown in Tables 1 and Figure 2 As shown, gelation occurs during the slurrying process. After deducting the charge capacity of lithium cobalt oxide in Comparative Example 1, the charge capacity of lithium supplement LFO is calculated to be 678.6 mAh / g. The positive electrode slurrying takes 12 hours.
[0062] Comparative Example 3: (1) Environmental requirements are the same as those in Example 1. Materials are weighed according to the formula VGCF: SP: nickel cobalt manganese oxide (NCM811): binder in a ratio of 0.5:1.5:100:2. VGCF is a conductive agent slurry with a content of 5%. A double planetary stirring kettle is used for mechanical stirring. First, an appropriate amount of NMP is added, and the binder is dispersed, the conductive agent SP is dispersed (taking 2 hours), and the nickel cobalt manganese oxide is dispersed. Finally, VGCF is added for dispersion. Continue to add an appropriate amount of NMP to adjust the slurry to a suitable viscosity, and remove bubbles to obtain a positive electrode slurry. Use a coating machine to apply the slurry to the positive electrode collector. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. Part of the positive electrode slurry is retained and left to stand for 8 hours to observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and initial efficiency tests are performed. The results are shown in Tables 1 and Figure 3 As shown, the slurry preparation process and the slurry standing for 8 hours did not gel. The charge capacity of lithium nickel cobalt manganese oxide in Comparative Example 3 was 233.47 mAh / g. The positive electrode slurry preparation took 10 hours.
[0063] Comparative Example 4: The environmental requirements are the same as those in Example 1. Except for VGCF as a slurry with a content of 5%, the other materials are solid powders. Weigh the materials according to the formula VGCF: SP: LNO: nickel cobalt manganese oxide (NCM811): binder in a ratio of 0.5:1.5:2:100:2. Using a double planetary stirring kettle for mechanical stirring, first add an appropriate amount of NMP, and then disperse the binder, the conductive agent SP (taking 2 hours), the LNO (taking 2 hours), the nickel cobalt manganese oxide, and finally add VGCF to disperse. Continue to add an appropriate amount of NMP to adjust the slurry to a suitable viscosity, and remove bubbles to obtain a positive electrode slurry. Use a coater to apply the slurry to the positive electrode collector. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. Retain part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and first efficiency tests are carried out. The results are shown in Tables 1 and Figure 3 As shown, the slurry process did not gel, and gelled after standing for 8 hours. After deducting the charge capacity of lithium nickel cobalt manganese oxide in comparative example 1, the charge capacity of lithium supplement LNO was calculated to be 405.8 mAh / g. The positive electrode slurry took 12 hours.
[0064] Comparative Example 5: (1) Environmental requirements are the same as in Example 1. Materials are weighed according to the formula G: SP: lithium-rich manganese base: binder in a ratio of 0.4: 2.4: 100: 2. Where G is a conductive agent slurry with a content of 4%. A double planetary stirring kettle is used for mechanical stirring. First, an appropriate amount of NMP is added, and the binder is dispersed, the conductive agent SP is dispersed (taking 2 hours), and the lithium nickel cobalt manganese oxide is dispersed in turn. Finally, G is added for dispersion. Continue to add an appropriate amount of NMP to adjust the slurry viscosity to a suitable level, and remove bubbles to obtain a positive electrode slurry. Use a coating machine to apply the slurry to the positive electrode current collector. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. Part of the positive electrode slurry is retained and left to stand for 8 hours to observe whether it is gelled. The obtained positive electrode sheet is assembled into a button battery with a lithium sheet as the negative electrode, and the specific capacity and first efficiency test are performed. The results are shown in Table 1. There is no gelation during the slurry preparation process and the slurry is left to stand for 8 hours. The charging specific capacity of the lithium-rich manganese base in Comparative Example 3 is 304.79 mAh / g. The positive electrode slurry preparation took 10 hours.
[0065] Comparative Example 6: The environmental requirements are the same as those in Example 1. Except for the slurry with a content of 4% by G, the rest of the materials are solid powders. Weigh the materials according to the formula G: SP: LFO: lithium-rich manganese base: binder in a ratio of 0.4: 2.4: 2: 100: 2. Using a double planetary stirring kettle for mechanical stirring, first add an appropriate amount of NMP, and then disperse the binder, disperse the conductive agent SP (taking 2 hours), disperse LFO (taking 2 hours), disperse lithium nickel cobalt manganese oxide, and finally add G to disperse. Continue to add an appropriate amount of NMP to adjust the slurry viscosity to a suitable level, and remove bubbles to obtain a positive electrode slurry. Use a coating machine to apply the slurry to the positive electrode current collector. Then, after drying, rolling and other processes, a positive electrode sheet is obtained. Retain part of the positive electrode slurry, let it stand for 8 hours, and observe whether it is gelled. The obtained positive electrode sheet is assembled into a buckle with a lithium sheet as the negative electrode, and the specific capacity and first effect tests are performed. The results are shown in Table 1, and gelation occurs during the pulping process. After deducting the specific charge capacity of the lithium-rich manganese-based electrode in comparative example 5, the specific charge capacity of the lithium supplement LFO was calculated to be 672.8 mAh / g. The preparation of the positive electrode slurry took 12 hours.
[0066] The test results of all embodiments and comparative examples are shown in Table 1.
[0067] The specific charging capacity of the lithium supplement agent is calculated based on the first charging capacity of the embodiment and the comparative example. Figure 2 It can be seen that the gram capacity of the lithium supplement agent LFO in Examples 1-4 is above 780mAh / g, which is significantly higher than the result of 678mAh / g in Comparative Example 2 in which the lithium supplement agent LFO and the conductive agent powder are directly used. The results of Examples 8, 9 and Comparative Example 6 also support the above conclusion. The gram capacity of the conductive lithium supplement composite functional slurry LNO used in Examples 5-7 and Comparative Example 4 and the table is higher than that of directly using LNO and the conductive agent powder. The slurry gel experiment results show that the positive electrode slurry did not gel during the slurrying and 8h standing process using the conductive lithium supplement composite functional slurry of the present invention. Comparative Examples 2 and 6 show that the direct use of LFO powder will cause the positive electrode slurry to gel during slurrying. Direct use of LNO powder will cause the slurry to gel during the standing process. Finally, the slurrying time data shows that the use of conductive lithium supplement composite functional slurry can shorten the slurrying time by 2-4h without the dispersion step of carbon black conductive agent and lithium supplement powder. In summary, the solution provided by the present invention is effective in improving battery performance, improving positive electrode slurry gel and shortening slurry preparation time, and has positive significance for the production of lithium-ion batteries.
Claims
1. A conductive lithium-supplementing composite slurry, characterized in that: The invention comprises a conductive agent, a lithium supplement agent and a solvent, and does not contain a binder PVDF.
2. The conductive lithium-supplementing composite slurry according to claim 1, characterized in that: Also included is a thickener, which includes one or more of povidone, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose.
3. The conductive lithium-supplementing composite slurry according to claim 2, characterized in that: The mass ratio of the conductive agent, the lithium supplement agent, the thickener and the solvent is 0.1-10:1-20:0.3-5:
100.
4. The conductive lithium-supplementing composite slurry according to claim 1, characterized in that: The conductive agent comprises a nanoscale conductive agent and a carbon black conductive agent, wherein the nanoscale conductive agent comprises one or more of single-walled carbon nanotubes, carbon nanotubes, vapor-grown carbon nanofibers and graphene, and the carbon black conductive agent is one or more of Super P Li, Ketjen black, acetylene black and 350G; the mass ratio of the nanoscale conductive agent to the solvent is (0.1-5):100, and the mass ratio of the carbon black conductive agent to the solvent is (1-10):
100.
5. The conductive lithium-supplementing composite slurry according to claim 1, characterized in that: The lithium supplement agent includes one or both of lithium-rich lithium iron oxide and lithium-rich lithium nickel oxide, and the solvent is N-methylpyrrolidone.
6. A method for preparing a conductive lithium-supplementing composite slurry, characterized in that: The following steps are involved: Under a dry environment, conductive agent powder, lithium supplement agent powder, thickener and solvent N-methylpyrrolidone are weighed, the thickener is mechanically stirred and dissolved in the solvent, and then the nano-scale conductive agent is added for ultrasonic dispersion, and then the carbon black conductive agent is added for mechanical stirring and dispersion, and finally the lithium supplement agent is added and stirred under vacuum conditions to obtain a uniform suspension, and the conductive lithium supplement composite slurry is obtained after adjusting the viscosity and removing bubbles.
7. The preparation method according to claim 6, characterized in that: The viscosity of the conductive lithium-supplementing composite slurry is 3000-20000 mPa.s, and the slurry fineness is ≤30 μm; the environmental conditions are dew point ≤-40° C., and the vacuum degree during vacuum stirring is ≤-90 kPa.
8. An application of the conductive lithium-supplementing composite slurry according to any one of claims 1 to 5 or the conductive lithium-supplementing composite slurry prepared by the preparation method according to claim 6 or 7, characterized in that: The conductive lithium-supplementing composite slurry is used for the preparation of positive electrode slurry, the positive electrode slurry contains a binder PVDF, and no other conductive agent and lithium-supplementing agent need to be added during the preparation. The conductive lithium-supplementing composite slurry is added after the raw materials of the positive electrode material are dispersed and before the viscosity adjustment step; the amount of the conductive lithium-supplementing composite functional slurry is calculated according to the mass ratio of the sum of the mass of the conductive agent and the lithium-supplementing agent to the mass of the positive electrode active material, which is 0.5-10:
100.
9. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode membrane disposed on the positive electrode current collector, wherein the positive electrode membrane contains the conductive lithium-replenishing composite slurry described in any one of claims 1 to 5 or the conductive lithium-replenishing composite slurry prepared by the preparation method described in claim 6 or 7.
10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Preparation method of carbon-coated lithium-rich lithium ferrite as well as obtained product and application of carbon-coated lithium-rich lithium ferrite
CN115642232A
Carbon-coated lithium-rich lithium ferrite and preparation method thereof, positive electrode lithium supplementing material and application
CN117199276A